Looking out into the fog: narrative, historical responsibility, and the problem of freedom in Kazuo Ishiguro's The Buried Giant. Issue 1 (2nd January 2021) - Stacy, Ivan
ABSTRACT: Kazuo Ishiguro used his 2017 Nobel lecture to suggest that liberal democracies have failed to take advantage of the opportunities presented in the late twentieth century, and a new sense of anxiety is evident in The Buried Giant . While Ishiguro's early novels celebrated the freedom of expression available to those living in democratic societies, The Buried Giant explores the tensions between narrative and historical responsibility, and suggests that an excess of such freedom inevitably leads to conflict. The novel conducts this exploration through its use of fantasy, and specifically through the way that the landscape makes literal what would otherwise be figurative ways of discussing memory: memory is eroded by a magical mist, is buried beneath the ground, and is irrevocably erased by a journey across water. This landscape embodies the dangers of two opposing views. These are, firstly, the postmodern notion that history is a narrative construction and, secondly, the idea that history is an objective truth that can be retrieved. The article concludes by arguing that The Buried Giant seeks to mediate between these two extremes, proposing that ethical narrative must be constructed on the basis of a recognition of others' experiences of the past.